Pengembangan Media Pembelajaran Berbasis Augmented Reality pada Mata Pelajaran Informatika Kelas VIII di SMPN 1 Karangan - Ramdhanti, Wahyu Andria; Rozi, Fahrur; Indrakusuma, H. Abdul Haris (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the limited use of interactive learning media in Informatics subjects which has an impact on low student engagement in the learning process. This study aims to develop and test the feasibility of Augmented Reality-based learning media on computer hardware material for eighth grade students. The study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility of the product is assessed through validation by media experts and material experts, then tested on 10 students in small groups and 32 students in large groups. Data were collected using validation sheets and student response questionnaires, then analyzed using descriptive percentage analysis. The results showed that the media obtained a validation score of 95.56% from media experts, 91.38% from material experts, 95.83% from small group trials, and 94.75% from large group trials, all of which are in the very feasible category. Thus, the Augmented Reality-based learning media developed is declared suitable for use as an Informatics learning medium for computer hardware material because it is able to provide a more interactive learning experience and facilitate visualization of the material.